Paul Ricoeur's Hermeneutic Analysis on User Interface Design for Augmented Reality Baleganjur Applications - I Komang Try Adi Stanaya; I Made Gede Arimbawa (Mudra Jurnal Seni Budaya, 2024)
Augmented reality technology or more popularly known as AR is a technology that implements interactive multimedia concepts. Augmented reality technology is a technology that combines the virtual world with the real world in real-time, through electronic devices such as cameras, sensors and software, augmented reality is able to display virtual objects in both 2D and 3D form in the real world. In this study, it focuses on analyzing the appearance of the interface design or the main menu application user interface by implementing augmented reality technology, with the name of the application, Augmented Reality Baleganjur. The user interface display on the main menu of the Baleganjur Augmented Reality application has design elements that can be translated with different meanings and understandings, depending on the user's point of view. This is the basis of this research, where the appearance of the user interface design on the main menu of the Baleganjur Augmented Reality application has design elements that can lead to different interpretations of meaning and understanding. The purpose of this study is of course to reveal the meaning and understanding of the design elements in the user interface design display of the Baleganjur Augmented Reality application, by conducting an in-depth analysis using Paul Ricoeur's Hermeneutics. As for the results of this study, it can be concluded that researchers as hermeneutics have an important role in interpreting and offering solutions, which can later be used as a reference for repairing or perfecting design elements in the application user interface, so that these design elements can convey meaning and understanding in a comprehensive and detailed manner to users.